Nomeação de unidades educacionais municipais de Goiânia: tecituras históricas e políticas (1960-2023) - Moura, Jaquelline (2024)
The objective of this dissertation, which is interdisciplinary and limited to the areas of history of education and toponymic studies, is to problematize the names of municipal educational units in Goiânia. Therefore, we resort to sources such as digital periodicals, official documents from the Secretaria Municipal de Goiânia (SME), the Diário Oficial de Goiânia and other documents. We adopt considerations from the History of Educational Institutions as a theoretical reference in an attempt to analyze the subject considering the contradictions in order to understand that the choice of names for educational units is associated, among others, with historical, political, cultural and social contexts. This study focuses on the analysis of names of religious, civil and military social entities that reveal how the act of naming configures power and status, something naturalized in our daily lives. Understanding the process of transferring the capital of Goiás and the consolidation of the SME in the municipality, officially created in 1961, allowed us to think about the construction of local history. For this, we have as reference the studies by Clímaco (1991), Bittar (1993) and Jesus (2004). Regarding the results, we can affirm that there is a preference for legitimizing names linked to privileged social classes and an attempt to erase the history of the trajectories of women who mostly occupy the teaching staff of Basic Education throughout the country. There is also a strong interference of the Christian religion in the educational sphere, which appropriates public spaces considered secular. Finally, it became clear that there is a need to renew research into the history of education in Goiânia, which will soon be one hundred years old.